The clustering of america - Weiis, Michael J. (New York: Haper y row)
Contents: 1. the clasterning of america. 2. cluster climbig. 3. the myth of the average american. 4. the way we work. 5. where the money goes. 6. love, american zip code style. 7. politics: from precint to the presidency. 8. changing clusters. 9. freeze frame: the forty clusters. appendixes: where do you fit in?. qifestylt quiz.
Indice
Keywords: United States Social Condictions 1980; United States Social Like and Custons 1971